Risk factors for conversion surgery to total hip arthroplasty of a hemiarthroplasty performed for a femoral neck fracture. Issue 2 (March 2018) - Grosso, Matthew J.; Danoff, Jonathan R.; Thacher, Ryan; Murtaugh, Taylor S.; Hickernell, Thomas R.; Shah, Roshan P.; Macaulay, William
Introduction: The purpose of this study was to determine risk factors for conversion to total hip arthroplasty (THA) in patients originally treated with hemiarthroplasty (HA) for displaced femoral neck fractures. Methods: In this case-controlled study, we identified 54 patients who were treated with HA for femoral neck fracture (FNF) who subsequently underwent conversion to THA at our institution between 2003 and 2013. We randomly selected 142 control patients who underwent HA for a displaced FNF without conversion surgery during the same time period. We compared demographic data, implant parameters, and radiographic data between the groups to identify risk factors for conversion surgery. Results: In the univariate analysis, younger age at index surgery (mean 75 vs. 80 years, p = 0.006), higher body mass index (26.1 vs. 23.7, p = 0.031), bipolar prosthesis (20% vs. 36%, p = 0.024), absence of dementia (6% vs. 23%, p = 0.01), increased leg length compared to contralateral limb (6.5 mm vs. 0.2 mm, p<0.001), and increased HA femoral head size compared to the contralateral femoral head (2.7 mm vs. 1.5 mm, p = 0.02) were associated with a significantly increased risk of conversion surgery. In the multivariate logistic regression, decreased age at index surgery, no dementia, use of a bipolar head, and increased leg length discrepancy (LLD) were associated with risk of conversion. Conclusions: Patient characteristics, including younger age, increased BMI, and absence of dementia can lead to increased risk for conversion of HA to THA. Intraoperative considerations of head size and increase in ipsilateral LLD may increase the risk of conversion surgery. These factors should be considered by surgeons who employ HA for displaced FNFs.